Kerasnya Rezim Orde Baru dalam Novel Laut Bercerita Karya Leila Chudori - Agustin, Bunga Auliya; Raharjo, Resdianto Permata (Jurnal Bahasa dan Sastra, 2024)
This study aims to investigate the historical context and messages contained in the novel Laut Bercerita, with the aim of enriching our understanding of the past that shaped the nation’s identity. The main themes in the novel are analyzed to relate them to the historical and political context of the New Order era, in the hope of opening up insights into the political and social circumstances of the time. The research method uses a literature approach by analyzing relevant literature sources. The results showed that the novel Laut Bercerita depicts the struggle of activists in the New Order era against the authoritarian government that ignored the fate of the small people. The characters of the activists who are brave, passionate, caring for others, and critical are considered as role models. From this novel, we are reminded of the dangers of authoritarian regimes that suppress critical voices, the importance of continuing to fight for truth and justice, and not forgetting Indonesia’s dark history during the New Order era. By remembering the suffering, it is hoped that future generations can fight for the values of freedom and justice.